2020
DOI: 10.21608/ejfs.2020.23810.1041
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Contents, Comparative Antioxidant Studies and Anti-Tubercular Activities of Commonly Used Spices in Abuja, Nigeria

Abstract: S PICES are reported to be helpful against diseases of oxidative stress such as cardiovascular diseases and exhibit antimicrobial properties. The potential for their use as adjuvants in tuberculosis cases have not been explored. In this study, the in vitro antioxidant and antituberculosis activities of nine Nigerian spices (Syzigium aromaticum, Thonnigii sanguinea, Piper nigrum, Zanthoxylum zanthoxyloides, Zingiber officinale, Cyperus articulatus, Xylopia aethiopica, Lepidum sativum, and Nigella Sativa) along … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
(13 reference statements)
0
0
1
Order By: Relevance
“…Tannin content was found to be lower in this study than previously reported for spices [ 48 , 49 ]. However, when the effects of extraction solvents were compared, it was revealed that ethanol and methanol extracted tannins more effectively than acetone [ 25 ].…”
Section: Resultscontrasting
confidence: 78%
“…Tannin content was found to be lower in this study than previously reported for spices [ 48 , 49 ]. However, when the effects of extraction solvents were compared, it was revealed that ethanol and methanol extracted tannins more effectively than acetone [ 25 ].…”
Section: Resultscontrasting
confidence: 78%